Perspectives of key stakeholders about vocational training and rehabilitation in Trinidad and Tobago. (November 2016) - Terrana, Alexandra; Dowdell, Joanna; Edwards, Brydne; Tahsin, Farah; Cacciacarro, Lucia; Cameron, Debra
Introduction: Vocational training and rehabilitation programs are effective in increasing employability and community participation of individuals with intellectual disabilities. Much of the research on effective programming has been conducted in high-income countries with resources targeted at individuals with intellectual disabilities. Although Trinidad and Tobago is a high-income country, there is a dearth of services and resources available to individuals with intellectual disabilities. This article explores stakeholder perspectives on the current status of vocational training and rehabilitation programs for individuals with intellectual disabilities in Trinidad and Tobago. Method: Participants from diverse groups were identified through snowball sampling. Data were collected in the form of semi-structured interviews conducted in person in Trinidad and Tobago and ranging from 45 to 75 minutes in duration. Interviews followed a loose structure of open-ended questions and the person–environment–occupation model helped inform the questions. Results: Thirty participants completed the interviews including clients, parents, teachers, principals, non-governmental organization representatives and occupational therapists. Several themes and subthemes emerged including balancing the need for inclusion and segregation, stigma, social policy, issues in current vocational services and independence and expectations. Conclusion: Vocational services in Trinidad and Tobago face many challenges including resource shortages and meeting the varying needs of clients. They also provide important safe spaces for socialization and acceptance. Resources are needed to improve the level of current services and to help address the competing and at times contradictory goals of differing stakeholders.